Utilizing Games for Learning: Applications of Game-Based Training and Gamification. (November 2019) - Griggs, Andrew; Lazzara, Elizabeth H.; Palmer, Evan; Fouquet, Sarah; Leverenz, Tiffany; Raushel, Alexis; Doherty, Shawn
Games are now beginning to receive growing attention in domains outside of entertainment. Applied settings are increasingly utilizing games in the development and implementation of various training programs. Two prevalent methods for the utilization of games in training include game-based learning and gamification. The utilization of games in training can improve participant motivation and engagement, but best practices for the use of games in training are not well defined. This panel will discuss various projects that have applied game-based learning and gamification in training efforts across a variety of industries.